Flexural behavior of delta and bi-delta cold-formed steel beams: experimental investigation and numerical analysis - Yazid Hadidane; Nadia Kouider; Mohammed Benzerara (Fracture and Structural Integrity)
Cold-formed steel (CFS) structural members retain their preferred position in the lightweight construction industry, which is due to their significant advantages. The optimization of these CSF elements will make it possible to construct buildings at very competitive prices, having in addition an increased load capacity, and thus obtaining a stable and economical construction. The main objective of this research being the evaluation of the effectiveness of these new sections in (CSF) and the estimation of the remarkable instabilities as well as the failure modes. This article deals with an experimental study on the behavior of CSF beams of delta and bi-delta shape, solicited by four-point bending loads. These cross section shapes are often used in floors as main and secondary beams. The properties of this type of sections are most often based on the method involving the effective width designated by the Eurocode 3 standard. A nonlinear analysis by finite elements (FE) using the ABAQUS calculation program is carried out, thus making it possible to compare the experimental results with the numerical ones as well as those which are given by the theory proposed by Eurocode 3. Finally, the results obtained essentially showed that the failure modes of the delta and bi-delta beams corresponded to the buckling modes local.